Sexual and Reproductive Health Trends Among Women With Enduring Mental Illness: A Survey of Western Australian Community Mental Health Services - Hauck, Yvonne; Nguyen, T.; Frayne, J.; Garefalakis, M.; Rock, D. (Taylor and Francis Inc., 2015)
© 2015, Copyright © Taylor & Francis Group, LLC. An exploratory cross-sectional survey was conducted to determine associations and potential modifiable risk factors for management of sexual and reproductive health needs for women attending community mental health services. Women (n = 220) had on average three pregnancies; 61.2% were unplanned. One quarter who were sexually active within the past 12 months denied using contraception with 51% using less effective methods. The majority (81.7%) engaged in Pap smear screening, and those with a general practitioner (GP) were more likely to participate (p =.004). Findings highlight GPs’ potential in optimizing women's health. Considering unplanned pregnancies and contraception trends, we suggest improved access to contraception options, particularly long-acting reversible methods.